The Significance of Hypotheses - Chesterman, Andrew (TTR)

(untitled) (Association canadienne de traductologie, 2011)
The paper examines the idea that all research methodology is based on hypotheses of different kinds, both interpretive and empirical. Interpretive hypotheses (that something is usefully interpreted as something) can be tested pragmatically, but are not falsifiable; they underlie all empirical research. As an example of empirical hypotheses we focus first on the descriptive type, and in particular the literal translation hypothesis. This states that translators tend to proceed from more literal to less literal versions as they process a given text chunk. This hypothesis serves to illustrate the main criteria according to which any hypothesis can be claimed to be significant. These criteria are: explicitness, multiple testability, theoretical implications, applicability, surprise value, and explanatory power. Several other fairly well-known hypotheses in Translation Studies are also referred to.